2016
DOI: 10.5897/ajmr2016.8222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature, pH and substrate composition on production of lipopeptides by Bacillus amyloliquefaciens 629

Abstract: The lipopeptides surfactin, fengycin and iturin produced by Bacillus species have diverse ecological roles, including antimicrobial activity, induced systemic resistance in plants against pathogens and plant colonization by the producing strain. The conditions that govern both lipopeptide production and plant colonization are not fully understood. The present study investigated the role of growth media, temperature and pH on the production of the lipopeptides surfactin, fengycin and iturin by Bacillus amyloliq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 33 publications
(36 reference statements)
0
1
0
2
Order By: Relevance
“…Little is known about the effects of low or fluctuating temperature on the production of BSMs by Bacillus spp. Several studies have reported an increase in lipopeptide production with decreasing temperatures (Fickers et al, 2008;Pertot et al, 2013;Pereira Monteiro et al, 2016;Chen et al, 2019). Growth at low temperatures (15°C) led to a marked increase in surfactin production in comparison to high temperatures (>35°C) (Pertot et al, 2013).…”
Section: Factors Influencing the Production Of Bioactive Secondary Me...mentioning
confidence: 98%
“…Little is known about the effects of low or fluctuating temperature on the production of BSMs by Bacillus spp. Several studies have reported an increase in lipopeptide production with decreasing temperatures (Fickers et al, 2008;Pertot et al, 2013;Pereira Monteiro et al, 2016;Chen et al, 2019). Growth at low temperatures (15°C) led to a marked increase in surfactin production in comparison to high temperatures (>35°C) (Pertot et al, 2013).…”
Section: Factors Influencing the Production Of Bioactive Secondary Me...mentioning
confidence: 98%
“…Para su biosíntesis es importante la participación de una enzima denominada fosfopanteteinil transferasa (PPT), la cual es codificada por el gen sfp (Mootz et al, 2001). Esta enzima es esencial en la activación de los dominios ACP En este contexto, se pudo demostrar que la cepa de B. amyloliquefaciens 629, es capaz de producir iturinas, fengicinas y surfactinas a nivel in vitro bajo diferentes condiciones de temperatura y medios de cultivo (Monteiro et al, 2016). Sin embargo, estos mismos autores reportan que esta bacteria es incapaz de producir estos compuestos en presencia de la planta.…”
Section: Producción De Sustancias Antimicrobianasunclassified
“…Estos mecanismos incluyen producción de compuestos antimicrobianos, producción de compuestos orgánicos volátiles (VOCs), síntesis de enzimas líticas, colonización y formación de biopelícula e inducción de resistencia vegetal (Ongena y Jaques, 2008;Shafi et al, 2017). Varios estudios ponen en evidencia la producción de compuestos antimicrobianos y VOCs a nivel de caja de Petri y en ensayos in vitro (Mosquera et al, 2014;Mora et al, 2015;Xie et al, 2018), sin embargo, este fenómeno no puede extrapolarse a la interacción con la planta y el patógeno o lo que suele denominarse el sistema tritrófico (Chowdhury et al, 2015b;Monteiro et al, 2016). Esto se debe a que hay diferentes factores que influyen en la determinación del papel de cada uno de los mecanismos en la acción biocontroladora, como el hecho de que la interacción con la planta tiene una gran complejidad en términos de comunicación molecular y bioquímica (Yuan et al, 2015).…”
Section: Introductionunclassified